A label-free electrochemical aptasensor based on a gold nanoparticle/carbon nanotube/metal–organic framework nanohybrid for ultrasensitive detection of streptomycin in milk samples. (15th February 2023) - Hui, Yuanyuan; Yang, Ding; Wang, Weizhe; Liu, Yingying; He, Chao; Wang, Bini
Highlights: A label-free sensing interface was designed for the detection of streptomycin. Au@P-N-CNT/PEI–MIL-101(Cr) composites were used as an effective sensing platform. The aptasensor showed high sensitivity and selectivity. The aptasensor could be proposed for monitoring other antibiotics in foodstuffs. Abstract: In this work, a novel electrochemical aptasensor was designed for the sensitive and specific detection of STR in milk samples. First, a gold nanoparticle@poly(diallyldimethylammonium chloride) nitrogen-doped carbon nanotube/polyethyleneimine-functionalized metal–organic framework (MOF) (Au@P-N-CNT/PEI–MIL-101(Cr)) composite was synthesized and characterized by various technique. The Au@P-N-CNT/PEI–MIL-101(Cr) composite was then modified on a bare glassy carbon electrode (GCE) surface, providing a favorable platform (Au@P-N-CNT/PEI–MIL-101(Cr)/GCE) for aptamer immobilization and current signal amplification. The STR aptamer was grafted to the Au@P-N-CNT/PEI–MIL-101(Cr)/GCE through the formation of Au–S bonds and π–π stacking interactions. The immobilized STR aptamer binds specifically STR, resulting in an obvious decrease in the current signal. Under the optimal experimental conditions, the linear range of the electrochemical aptasensor for STR detection was 0.01–250 nM which the detection limit (LOD) was calculate as 2.31 nM. This strategy is expected to be a novel platform for the rapid and sensitive detection of STR.